183. Alerting and Education via the Electronic Health Record (EHR) Decreases Inappropriate Fluoroquinolone prescribing in the Emergency Department of a Large Integrated Hospital Network. (26th November 2018) - Davidson, Lisa; Medaris, Leigh Ann; Agner, Tammi; Kowalkowski, Marc; Sullivan, D Matthew
Abstract: Background: Emergency department (ED) providers frequently use fluoroquinolones (FQs) as first-line therapy for common infections in discharged patients. In 2016 the FDA issued a warning against FQ use for three common conditions: cystitis, bronchitis, and sinusitis. This study evaluated the effect of an electronic health record (EHR) clinical decision support alert followed by targeted provider education on FQ prescribing in the ED. Methods: We performed a nonrandomized, single arm, pre–post study of FQ prescribing in target indications before (November 2015–October 2016) and after (January 2017–December 2017) implementation of an EHR alert at 19 hospital-based and free-standing EDs in the Charlotte NC area. Providers were alerted when a patient was discharged from the ED on an FQ with a target diagnosis (infections identified as being inappropriate for FQ) without additional exclusions (e.g., penicillin allergy) (Figure 1). Initial provider education on appropriate FQ use accompanied EHR alert implementation at all 19 participating EDs in November 2016. Targeted follow-up education was delivered in August 2017. We compared overall FQ prescribing rates in pre- vs. post-alert intervals using chi-squared tests. We compared FQ prescription volume following alert failure by indication for high alert failure diagnoses (ICD10 codes with ≥75 alerts) in Q1 2017 vs. Q4 2017. Results: Target population ED discharges remained stable pre- and post-alert implementation ( n = 37, 975; n = 37, 731). FQ prescribing decreased 53% from pre ( n = 13, 796, 36%) to post alert ( n = 7, 289, 19%; P < 0.01). While total orders avoided after alert firing remained low, the total prescriptions (i.e., alert overrides) dropped from 789 in January 2017 to 397 in December 2017 (Figure 2). The largest decrease was observed after repeat provider education in August 2017. Diagnosis categories with high volume alert failures decreased from 15 unique ICD10 diagnosis ( n = 1, 534 prescriptions) in Q1 2017 to 3 (diverticulitis, pneumonia, gastroenteritis/colitis; n = 419 prescriptions) in Q4 2017. Conclusion: Effective EHR alert implementation combined with timely and targeted provider education on appropriate prescribing reduces inappropriate ED provider FQ prescribing by more than 50%. Disclosures: L. Davidson, Duke Endowment: Grant Investigator, Grant recipient